Examining Autism Detection in Early Childhood (ADEC) in the Early Identification of Young Children with Autism Spectrum Disorders (ASD). (August 2016) - Young, Robyn L.; Nah, Yong‐Hwee
Abstract : Objective: Screening for autism spectrum disorder (ASD) is an important first step in the identification of children considered at risk of developing the disorder and in need of further assessment, intervention, and services. In this paper, we reviewed some commonly used ASD‐specific screening tools and focused on the use of an ASD‐specific screening tool developed in Australia, the Autism Detection in Early Childhood (ADEC), in enhancing the early identification of young children with ASD. The ADEC was developed as a clinician‐administered screening tool that was time‐efficient, suitable for children under 3 years, easy to administer, and suitable for persons with minimal training and experience with ASD. Method: A systematic search of published research studies was performed to review key findings of the ADEC and some commonly used ASD‐specific screening tools through February 2015. The Psych‐Info and Google Scholar online databases were searched concurrently for entries containing any combination of the terms (a) autism screening and (b) autism detection in early childhood. Results: We found four studies suggesting that screening for ASD using the ADEC can be sensitive and specific in children under the age of three. The ADEC is comparable to some commonly used ASD‐specific screening tools. Conclusions: Based on the studies presented, as compared to some commonly used ASD‐specific screening tools, the ADEC is a sound and effective ASD screening tool, suitable for use with young children ranging from 12–36 months of age, and can be used with confidence to compliment the developmental surveillance and assessment processes. There is also the potential and possibility of translating the ADEC across different socio‐economic populations, including developing and low‐resource countries.